Curious minds : 40 hands-on activities to inspire a love of learning - Kolstedt, Ty; Vasi, Azeem Z. (Zephyr Press, an imprint of Chicago Review Press Incorporated, 2016)
"A great resource for parents and homeschoolers in search of kid-friendly DIY projects, educators seedking to enhance classroom lessons, and cregivers or camp counselors looking for activities with a deeper educational lesson behind them"--Back cover.